Backside wear in acetabular hip joint replacement - Braun, Steffen; Sonntag, Robert; Schröder, Stefan; Müller, Ulrike; Jäger, Sebastian; Gotterbarm, Tobias; Kretzer, Jan Philippe (Acta biomaterialia, 2019)
Introduction - Besides head-insert articulation in hip joint replacements, micro-motions between the backside of assembled polyethylene acetabular liners and the metal cup may cause additional wear. Pelvic osteolysis frequently occurs in the region of screw holes, and cup loosening hints to clinically relevant amounts of polyethylene backside wear. It has yet to be confirmed whether backside wear particles differ in size and morphology compared to articulating wear. Previous methods have been limited to subjective assessment of backside surface damages without consideration of wear debris. The aim of this study was to develop and validate a method for quantitative in vitro measurements of polyethylene backside wear in artificial hip cups and to characterize these wear particles for the first time. - Methods - Titanium cup-systems (Plasmafit®Plus7, Aesculap, UHMWPE liner) were sinusoidally loaded (2.5kN) and a torque of 5Nm was simultaneously applied. The front and rear side of the cup were separated to isolate backside wear. After 2×106 cycles the surrounding fluid was filtered and a particle analysis was performed. - Results - Backside wear had a particles size of 64.1±1.9nm and was verified as round and oval particles with partly rough outlines. An estimated total number of particles of 1.26×109±1.67×108 per 106 cycles was determined. - Conclusion - Backside wear was estimated to be several times lower than published values of articulating wear. However, polyethylene backside wear particles represented significantly smaller particles with partly roughened outlines than articulating wear particles and may therefore cause higher biological response in macrophage-mediated bone resorption compared to articulated particles. - Statement of Significance - Within this study, an analytical method for quantitative measuring polyethylene backside wear of artificial hip cups was successfully developed and validated for the first time. It could be shown that backside wear is still present, even in modern cup-systems. These findings can be further used for investigations of the osteolytic potential of polyethylene particles, for evaluating and improving new implant systems and to evaluate the effectiveness of screw hole plugs to prevent the particle migration to the acetabulum.
Available online 5 November 2018
Gesehen am 26.07.2019